Impact Of Using Visual Feedback On Some Offensive Holds And Technical Performance For Greco-Roman Wrestlers - Tawheed Haider Abdul Razzaq; Rusul Salam Jaber; Rawnaq Hadi Faisal, (Musamus Journal of Physical Education and Sport (MJPES), 2026)
Greco-Roman wrestling is a combat sport that demands a high level of precision in technical execution and ability to execute offensive holds efficiently and quickly. With continuous development of modern training methods, use of technological tools, particularly visual feedback, has become an effective method for improving athletes' motor and technical performance. This helps wrestlers identify and immediately correct their mistakes by reviewing recordings of their training sessions, thus enhancing their ability to refine their movements and achieve optimal performance. Research problem lies in fact that many Greco-Roman wrestlers suffer from weak technical execution of certain offensive holds due to their reliance on traditional training methods that lack accurate and immediate feedback. This highlights importance of introducing modern visual tools that contribute to developing offensive efficiency and raising technical level of wrestlers. The research aims to identify effect of using visual feedback in developing some offensive holds and improving technical performance of junior Greco-Roman wrestling players. The researchers used experimental method because it is suitable for nature of research by applying a training program based on video and visual analysis of performance within specific periods and comparing results before and after implementation. This indicates that use of visual means in training is one of modern methods effective in developing skill and technical aspects of wrestling players. The researchers recommend generalizing this method in training centers and clubs because of its positive effect on raising technical level and general performance of players